2007
DOI: 10.1086/512850
|View full text |Cite
|
Sign up to set email alerts
|

Capture of Irregular Satellites during Planetary Encounters

Abstract: More than 90 irregular moons of the Jovian planets have recently been discovered. These moons are an enigmatic part of the solar system inventory. Their origin, which is intimately linked with the origin of the planets themselves, has yet to be adequately explained. Here we investigate the possibility that the irregular moons were captured from the circumsolar planetesimal disk by three-body gravitational reactions. These reactions may have been a frequent occurrence during the time when the outer planets migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
255
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 222 publications
(274 citation statements)
references
References 77 publications
17
255
0
2
Order By: Relevance
“…Our code checks this planet-planetesimal distance every 14 years. We define as t = t * the instant when a close approach between Uranus and a planetesimal occurs, such that the separation distance is ≤0.8 AU (Beaugé et al 2002;Nesvorný et al 2007;Nogueira 2008). Starting from t = t * , the planet-planetesimal system is integrated backward until t = t * * , when the separation distance becomes greater than 1.0 AU.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our code checks this planet-planetesimal distance every 14 years. We define as t = t * the instant when a close approach between Uranus and a planetesimal occurs, such that the separation distance is ≤0.8 AU (Beaugé et al 2002;Nesvorný et al 2007;Nogueira 2008). Starting from t = t * , the planet-planetesimal system is integrated backward until t = t * * , when the separation distance becomes greater than 1.0 AU.…”
Section: Methodsmentioning
confidence: 99%
“…It is clearly expected that the closer the satellite, the tighter the link to the planet. Tsiganis et al (2005), Nesvorný et al (2007), and others, found that the regular satellites undergo only minor perturbations during the planetary close encounters. The name "regular" satellite, in general, is given to those very close to the planet of small eccentricity and inclination.…”
Section: Regular and Irregular Satellitesmentioning
confidence: 96%
See 3 more Smart Citations